2013
DOI: 10.1310/tscir2001-44
|View full text |Cite
|
Sign up to set email alerts
|

Does Caregiver Well-Being Predict Stroke Survivor Depressive Symptoms? A Mediation Analysis

Abstract: Background and Purpose-Studies suggest that family caregiver well-being (ie,, depressive symptoms and life satisfaction) may affect stroke survivor depressive symptoms. We used mediation analysis to assess whether caregiver well-being might be a factor explaining stroke survivor depressive symptoms, after controlling for demographic factors and stroke survivor impairments and problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…The TASK II intervention is unique in that it is delivered completely by telephone, trains caregivers how to assess and address their own needs, and is applicable to a wide variety of stroke caregivers (e.g., spouses, adult children, others). Screening for and addressing caregiver depressive symptoms, as in the TASK II program, not only have the potential to improve caregiver outcomes, 10, 12, 19, 20 but may improve the survivors’ recovery 15 and reduce the potential for their long-term institutionalization. 9, 17, 18 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TASK II intervention is unique in that it is delivered completely by telephone, trains caregivers how to assess and address their own needs, and is applicable to a wide variety of stroke caregivers (e.g., spouses, adult children, others). Screening for and addressing caregiver depressive symptoms, as in the TASK II program, not only have the potential to improve caregiver outcomes, 10, 12, 19, 20 but may improve the survivors’ recovery 15 and reduce the potential for their long-term institutionalization. 9, 17, 18 …”
Section: Discussionmentioning
confidence: 99%
“…8, 9, 1113 Furthermore, the caregiver’s emotional well-being can influence the stroke survivor’s depressive symptoms. 1416 In addition, the caregiver’s depressive symptoms can affect the stroke survivor’s recovery, 15 communication, social participation, and mood. 16 Finally, caregiver stress is a leading cause of institutionalization for stroke survivors and other older adults.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the presence of depressive symptoms is an important factor to assess when considering caregivers' abilities to provide care at home for the stroke survivor because of the potential negative impact on the caregiver as well as the survivor. 16,17 …”
mentioning
confidence: 99%
“…Findings from a study of 146 couples suggested that psychological well-being of family caregivers influences the well-being of relatives with stroke (Grant et al, 2013). Similarly, Barskova and Wilz (2007) found that family caregiver attitudes and emotional health contribute to cognitive and psychological recovery of their relatives with stroke.…”
mentioning
confidence: 99%